Analysis of Farmers Knowledge, Attitudes and Skills in Dealing with Foot and Mouth Disease (FMD) Cases in Central Lombok - Mardi, Husnul; Taqiuddin, Moh.; Sriasih, Made (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The role of farmers is a determining factor in the success of efforts to control Foot and Mouth Disease (FMD), especially the level of knowledge, attitude, and skills of farmers. This study aims to determine the correlation and influence between knowledge, attitude, and skills of farmers with the location and characteristics of farmers. The study was conducted using a survey method on samples selected purposively in three sub-districts, namely Praya Tengah, Pujut and Praya Barat Daya with a total of 100 respondent farmers. This study uses correlation analysis and linear regression for data analysis. The results of the study indicate that there is a correlation value between the level of knowledge, attitude and skills of farmers towards controlling FMD with the location and characteristics of farmers, including: gender, age, education level, occupation, ownership status, experience/length of farming and the number of cattle owned by the farmer. As well as the influence of the location of the farmers residence and the characteristics of the farmers on the level of knowledge, attitude and skills of the farmers.